Study on the Performance of Interactive Cascade Ventilation Oriented to the Non-uniform Indoor Environment Requirement - Li Han; Li Jinchao; Nana; Kong Xiangfei (Zhileng xuebao)
A new ventilation method called interactive cascade ventilation was proposed in this study to facilitate a healthy and comfortable indoor environment with low energy consumption. Interactive cascade ventilation can take full advantage of thermal buoyancy by optimizing the energy grade of mechanical ventilation and determining the temperature gradient between jets to transform the action direction of thermal buoyancy. This study investigated the performance of interactive cascade ventilation based on temperature distribution, energy utilization efficiency, and indoor thermal comfort. The research results showed that the average indoor temperature under interactive cascade ventilation increased by only 2.5℃ with a 25% reduction in cooling energy input compared with stratum ventilation. The ventilation effectiveness under interactive cascade ventilation was 1.004, which was higher than that under stratum ventilation. Moreover, thermal comfort significantly improved. The ADPI under interactive cascade ventilation was 0.852 4, while that under stratum ventilation was 0.841 7. In addition, the PMV under interactive cascade ventilation was better distributed and closer to a thermally neutral environment. Hence, interactive cascade ventilation can realize the improvement of energy application of mechanical ventilation in both quality and quantity by using different grade energies to create jets of different temperatures. It can provide new solutions to promote the creation of a non-uniform indoor environment and present important energy-saving, environmental protection, and social benefits.